Comparison of corticomotor excitability during visuomotor dynamic and static tasks - Pearce, A. J.; Kidgell, D. J. (Journal of Science and Medicine in Sport, 2010)
The human central nervous system (CNS) has the ability to modulate its activity during the performance of different movements. Recent evidence, however, suggests that the CNS can also modulate its activity in the same movement but with increased precision during a visuomotor static task. This study aimed to extend on these findings by using transcranial magnetic stimulation (TMS) to measure the CNS during the performance of two visuomotor dynamic tasks. Twelve volunteers participated in this study, performing two separate motor tasks. Study I ("Position Tracking") involved participants to perform a visuomotor tracking task using a dial potentiometer and matching their response icon to the computer generated tracking icon whilst holding a pincer grip. Study II ("Force Tracking") involved participants to perform a similar visuomotor tracking task by applying or releasing pressure against a fixed force transducer. Tasks were conducted at two speeds ("slow" being one tracking cycle in 10 s; and "fast" being two tracking cycles in 10 s) and compared to a visuomotor static task at a similar muscle contraction level. Results showed corticospinal changes with significant increases (p = 0.002) in excitability demonstrated during Study I (42.3 ± 16.8%) and Study II (56.3 ± 34.2%) slow speed tasks. Moreover, significant reduction in corticospinal inhibition was also observed during both tracking tasks at slow (59.3 ± 13.7%; p = 0.001) and fast speeds (31.9 ± 12.3%; p = 0.001). The findings may provide information on the underlying physiology during the early stages of motor skill acquisition.